Islamic Business Ethics: How to Apply it on the Supply Chain Management? - Agus Wahyu Irawan; Mukhamad Roni; Heri Kuncoro Putro; Moh. Agus Sifa' (JOURNAL OF SHARIA ECONOMICS, 2021)
The purpose of this research was analyzing the application of Supply Chain Management in the perspective of Islamic business ethics. Islamic business ethics is related to the implementation of Supply Chain Management in related companies, from the purchasing process of production, retail distribution to consumption by the public. There needs to be a concept of applying Islamic business ethics as a basis for doing business. Business ethics are sometimes ignored by business people. By applying business ethics, a businessman can understand even very difficult business competition, how to maintain good manners, be friendly, how to dress properly and how to speak words to deal with customers, all of which has meaning. business people do everything they can to get high profits, even business people often ignore the ethics that must be considered in running a business. The method used in this research was qualitative research by using the document analysis. The results of this article on the application of Supply Chain Management in the perspective of Islamic business ethics were that every company when conducting its business must have elements of unity, justice, free will, responsibility and virtue.